2012
DOI: 10.1371/journal.pone.0041480
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded Multilocus Sequence Typing Scheme for Propionibacterium acnes: Investigation of ‘Pathogenic’, ‘Commensal’ and Antibiotic Resistant Strains

Abstract: The Gram-positive bacterium Propionibacterium acnes is a member of the normal human skin microbiota and is associated with various infections and clinical conditions. There is tentative evidence to suggest that certain lineages may be associated with disease and others with health. We recently described a multilocus sequence typing scheme (MLST) for P. acnes based on seven housekeeping genes (http://pubmlst.org/pacnes). We now describe an expanded eight gene version based on six housekeeping genes and two ‘put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
273
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(306 citation statements)
references
References 56 publications
16
273
3
3
Order By: Relevance
“…Our previous 16S ribosomal RNA metagenomic study demonstrated that P. acnes strain population structure in pilosebaceous units differs significantly between acne patients and healthy individuals (Fitz-Gibbon et al, 2013). Certain strains are highly associated with the disease (Lomholt and Kilian, 2010;McDowell et al, 2012;Fitz-Gibbon et al, 2013;Tomida et al, 2013), while some strains are enriched in healthy skin (FitzGibbon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous 16S ribosomal RNA metagenomic study demonstrated that P. acnes strain population structure in pilosebaceous units differs significantly between acne patients and healthy individuals (Fitz-Gibbon et al, 2013). Certain strains are highly associated with the disease (Lomholt and Kilian, 2010;McDowell et al, 2012;Fitz-Gibbon et al, 2013;Tomida et al, 2013), while some strains are enriched in healthy skin (FitzGibbon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the clade IA in healthy controls and acne patients was demonstrated in several studies, [19][20][21][22] as well as its dominance in acne patients. [23][24][25] While analysing the dominant phylotypes of C. acnes in 63 patients with mild to severe acne, Paugam et al 26 also observed that phylotypes IA1 and IA2…”
Section: Discussionmentioning
confidence: 99%
“…
AbstractObjective Our main objective was to compare Cutibacterium acnes (C. acnes) skin colonisation in patients with mild to moderate acne versus healthy controls and secondly, to evaluate a Myrtacine â -based cream on C. acnes total population and antibioresistant Cutibacteria in patients with acne.Methods In 60 acne patients (Global Acne Severity Scale, GEA grades 2-3), of mean age 20 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Results We first showed (i) high and similar levels of C. acnes colonisation in superficial pilosebaceous follicles and detection of EryR and ClnR strains in both acne and control groups; (ii) different repartition of phylotypes in acne patients versus healthy control, with a predominance of phylotype IA in acne patients and a link between phylotype IA and erythromycin resistance. Besides, after treatment with the Myrtacine â -based cream in acne patients, there was no change in C. acnes total load, but a significant decrease of EryR Cutibacteria, reduced porphyrin production by C. acnes, a decrease in acne severity (GEA), associated with reduced retentional and inflammatory lesions.

Conclusion Cutibacterium acnes colonisation was not significantly different in acne versus control groups.

…”
mentioning
confidence: 99%
“…The relative sequence abundance of Propionibacterium was significantly higher in controls than in patients with CSOM. Members of the genus Propionibacterium are part of the normal microbiota of the skin, mouth, and gut (57)(58)(59)(60). They are believed to play a role in stabilizing the normal microbiota by occupying niches which then cannot be invaded by pathogens (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Propionibacterium are part of the normal microbiota of the skin, mouth, and gut (57)(58)(59)(60). They are believed to play a role in stabilizing the normal microbiota by occupying niches which then cannot be invaded by pathogens (58,59). Moraxella is a known pathogen of the human respiratory tract, typically causing pneumonias in adults and acute otitis media in children (48).…”
Section: Discussionmentioning
confidence: 99%